Efeito da administração de alendronato, a longo prazo, sobre as propriedades mecânicas do tecido ósseo, sua reparação e mineralização ao redor de implantes osseointegráveis. Estudo em ratas - Verzola, Mario Henrique Arruda [UNESP] (2014)
The aim of this study was evaluate in female rats, the effect of long-term therapy with bisphosphonate on the healing process and bone mineralization around implants and on the mechanical properties of bone tissue. One hundred sixty female rats were randomly allocated into two equally sized groups: the alendronate (ALD) group, which received the subcutaneous administration of alendronate (1 mg/kg/week), and the control (CTL) group which the animals received weekly the subcutaneous administration of saline solution (placebo) for the entire experimental period. After 120 days of the treatment initiation, in the booth groups, one titanium implant was installed in the tibia metaphysis. Ten animals in each group were euthanized at: 5, 10, 15, 20, 25, 30, 45, or 60 days after surgery, and their femurs and tibias were removed. The femurs were evaluated regarding bone mineral density (BMD), and mechanical tests. The tibias samples with the implants were evaluated by removal torque, histometric analysis (% BIC and % BAFO), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS), mapping of mineralization and arrangement and distribution of the collagen. The results regarding bone densitometry showed higher values for the animals of ALD group compared with the CTL group at all evaluation periods, except for the period of 15 days. The results of mechanical tests, in general, showed higher fracture resistance (maximum force) and higher capacity of energy absorption (tenacity) in the ALD group compared with the CTL group until the 45 day. In the 45 days, the stiffness showed significantly higher values in the ALD group, however at 60 days no difference was observed between the groups. Regarding the resilience, the ALD group showed significantly higher values in the 45 days. The drug influenced the removal torque of implants with significantly higher values for ALD group until ...(Complete abstract electronic acess below)